Patient-derived induced pluripotent stem cells to study non-canonical splicing variants associated with Hypertrophic Cardiomyopathy - Joanna Jager; Marta Ribeiro; Marta Furtado; Teresa Carvalho; Petros Syrris; Luis R. Lopes; Perry M. Elliott; Joaquim M.S. Cabral; Maria Carmo-Fonseca; Simão Teixeira da Rocha; Sandra Martins (Stem Cell Research)
Hypertrophic cardiomyopathy (HCM) is the most prevalent inherited cardiomyopathy and a leading cause of sudden death. Genetic testing and familial cascade screening play a pivotal role in the clinical management of HCM patients. However, conventional genetic tests primarily focus on the detection of exonic and canonical splice site variation. Oversighting intronic non-canonical splicing variants potentially contributes to a proportion of HCM patients remaining genetically undiagnosed. Here, using a non-integrative reprogramming strategy, we generated induced pluripotent stem cell (iPSC) lines from four individuals carrying one of two variants within intronic regions of MYBPC3: c.1224-52G > A and c.1898-23A > G. Upon differentiation to iPSC-derived cardiomyocytes (iPSC-CMs), mis-spliced mRNAs were identified in cells harbouring these variants. Both abnormal mRNAs contained a premature termination codon (PTC), fitting the criteria for activation of nonsense mediated decay (NMD). However, the c.1898-23A > G transcripts escaped this mRNA quality control mechanism, while the c.1224-52G > A transcripts were degraded. The newly generated iPSC lines represent valuable tools for studying the functional consequences of intronic variation and for translational research aimed at reversing splicing abnormalities to prevent disease progression.